Utilization of probabilities in the preparation of financial information: Perspectives from International Financial Reporting Standards - Castañeda Moreano, Rosa Milagros (2023)
Objective: To analyze the concept of probability that is described in the International Financial Reporting Standards (IFRS). Method: Qualitative, partially descriptive, focused on content analysis of previous literature and the IFRS regulatory framework. The unit of study was the concept of probability. Results: The findings highlight the importance of using probabilities in the normative framework of IFRS, emphasizing the analysis of various scenarios regarding the future. Moreover, a thorough understanding of probability theory is crucial to have a clear conception of the term "probability" and its proper interpretation. Conclusion: It is necessary to analyze the various scenarios about the future from the Bayesian approach and fully comprehend its interpretation. Additionally, it is important to address the lack of precision in the term "probability" and its impact on its application in the preparation of financial statements.